2021
DOI: 10.7759/cureus.16350
|View full text |Cite
|
Sign up to set email alerts
|

A Study to See the Effect of Social Media Usage Among Healthcare Providers

Abstract: This study aimed to assess how healthcare professionals (HCPs) use social media to determine how it influences the quality of patient care. Materials and methodsThis is a cross-sectional study conducted over eight months, between August 2020 and March 2021 using a questionnaire and checked amongst investigators. ResultsOne hundred fifty-eight participants had electronic devices and 145 (91.9%) used social media at work. 26.6% of these HCPs said they spent less than an hour on social media forums, 31% said they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…It is interesting to compare the current findings to the small existing literature on the use of blogs to promote knowledge exchange in healthcare research and practice. Our findings diverge from the study by Khan et al [14] where 46% of healthcare staff used social media (not just blogs) for work-related tasks such as medical reading, and 11% engaged in online medical forums. It must be noted that the latter was conducted in America where perhaps different policies are in place regarding the use of social media at work.…”
Section: Increasing Blog Reach and Engagementcontrasting
confidence: 99%
See 1 more Smart Citation
“…It is interesting to compare the current findings to the small existing literature on the use of blogs to promote knowledge exchange in healthcare research and practice. Our findings diverge from the study by Khan et al [14] where 46% of healthcare staff used social media (not just blogs) for work-related tasks such as medical reading, and 11% engaged in online medical forums. It must be noted that the latter was conducted in America where perhaps different policies are in place regarding the use of social media at work.…”
Section: Increasing Blog Reach and Engagementcontrasting
confidence: 99%
“…Cheston et al 's systematic review [13] found that interventions using social media tools were associated with improved knowledge, attitudes, and skills, as well as promoting learner engagement, collaboration, feedback, and professional development. A cross-sectional study assessing the use of social media amongst healthcare professionals found that a substantial percentage (91.9%) of healthcare professionals used social media networks, with a sizeable proportion of doctors and nurses utilising this for work-related tasks such as medical reading, and engaging in online medical forums [14]. Similarly, the use of social media in medical education for physicians and physicians-in-training has proliferated.…”
Section: Knowledge Transfer In Palliative Dementia Carementioning
confidence: 99%
“…This may be more likely in fields like sport science, where employees are not required to have completed traditional academic pathways to work in the field. This is somewhat supported by research demonstrating that medical professionals use social media to support their own education (Khan et al, 2021), highlighting that even in "more academic" professions, practitioners regularly use social media to support their practice.…”
Section: Discussionmentioning
confidence: 97%
“…With the advent of telecommunication technologies and social media, many healthcare professionals are using social media to communicate with their patients and to promote health (M. N. Khan et al, 2021). However, the literature reveals a gap in our understanding of healthcare professionals' perceptions of their behavioral intentions to use innovations.…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of the Internet, social media marketing has become one of the most powerful tools and cost-effective ways to promote products and services. The use of social media sites by international companies as part of their promotion strategy has increased signi cantly in the past few years.With the advent of telecommunication technologies and social media, many healthcare professionals are using social media to communicate with their patients and to promote health (M. N. Khan et al, 2021). However, the literature reveals a gap in our understanding of healthcare professionals' perceptions of their behavioral intentions to use innovations.…”
mentioning
confidence: 99%